Analisis Implementasi Program Pos Pelayanan Terpadu Lanjut Usia (Posyandu Lansia) di Kelurahan Laksamana, Kecamatan Dumai Kota - Lilis Wahyuni; Dila Erlianti; Muhammad Azrin (Journal of Innovative and Creativity, 2025)
This research analyzes the implementation of the Integrated Service Post Program for the Elderly (Posyandu Lansia) in Laksamana Village, Dumai City District. Posyandu Lansia is a government initiative aimed at improving the health and well-being of the elderly through accessible and free services. The program includes various preventive, promotive, curative, and rehabilitative efforts to enhance the overall health of the elderly. In its implementation, the program involves cooperation between community health centers, villages, districts, and the Social Service, supported by trained cadres and active participation from the community and families of the elderly. The research findings indicate that the program's bureaucratic structure functions well, with activities that are structured and responsive to the needs of the elderly. A proactive, flexible, and informative approach ensures that the elderly receive tangible benefits from the provided services. Additionally, effective counseling increases the knowledge and awareness of the elderly regarding the importance of maintaining health. With support from various parties, the program successfully improves the health and well-being of the elderly, enabling them to live healthier, happier, and more independent lives. The study concludes that with a coordinated approach and support from various parties, Posyandu Lansia in Laksamana Village has been effectively implemented and has had a positive impact on the elderly.